Sago-Based Food Product Creation Training To Increase Competitiveness In The Market In Ngenang Island - Rosie Oktavia Puspita Rini; Afriani, Miratia; Mikasari, Dewi Aurora; Santika, Kamelia; Sihombing, Hans Steven (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
Community service with the topic